Data Protection by Design in Healthcare for Smart Cities: A Hardware-based Pilot using ARM Morello Board - Schuch, Regis; Teles-Borges, Mailson; Rodrigues, Diego Mendes; Sawicki, Sandro; Roos-Frantz, Fabricia; Frantz, Rafael Z. (Anais do Latin American Symposium on Digital Government (LASDiGov); 2026: Anais do XIV Latin American Symposium on Digital Government, 2026)
Smart and sustainable cities increasingly depend on integration processes to exchange data across their digital services, such as primary healthcare services. In conventional execution environments, the sensitive data handled by these processes remains exposed in memory, creating opportunities for unauthorised access, data exfiltration, and loss of institutional control over data processing. This paper reports the development and execution of the integration of digital services in a pilot project of a hardware-based approach using the ARM Morello Board. Our solution executes the integration process in a CHERI-based trusted execution environment and uses execution-environment attestation so that digital services can verify execution conditions before authorising them.